(untitled) (CIPEEX, 2026)
This study analyzes the relationship between planned obsolescence and child consumerism, highlighting the condition of hypervulnerability of children in consumer relations. Planned obsolescence is understood as the reduction of product lifespan through the use of artifices or materials of lesser durability, a practice that, combined with child advertising, compromises rights guaranteed by the Federal Constitution of 1988, the Consumer Defense Code, and the Child and Adolescent Statute. The consumer market has focused on children as potential consumers, encouraging them to desire more and more products and services, regardless of their real necessity. This logic characterizes modernity marked by ephemerality and the continuous disposal of things, as well as social bonds, reflecting directly on human consumption behavior and also on nature, with serious negative impacts on both. The research demonstrates that children, as hypervulnerable individuals, are the central target of marketing strategies that stimulate continuous consumption, reinforcing social inequalities and compromising their integral development, thus reinforcing social inequalities and violating constitutional principles.